Genome-wide association and selection studies for pod dehiscence resistance in the USDA soybean germplasm collection - JaeBuhm Chun; Sadal Hwang (PLoS ONE, 2025)
As a domestication trait, pod dehiscence has a pleiotropic effect on agronomic traits and significantly contributes to yield loss in soybean. Population studies are still required to comprehend the genetic basis of dehiscence and to develop pod dehiscence-resistant cultivars with the optimal haplotype, thereby improving soybean production. We collected data for one wild (Glycine soja) (G. soja) and four cultivated (Glycine max) (G. max) populations from the USDA database. The G. max populations were evaluated in multi-environment conditions and used for genome-wide association study (GWAS) and selection. GWAS captured 86 quantitative trait loci (QTLs). Seventy-four new QTLs were colocalized in two different G. max populations, and 12 QTLs were closely mapped with previously reported QTLs. Eight out of 86 QTLs were associated with the domestication of pod dehiscence. We implemented marker-assisted selection (MAS) and genomic selection (GS) approaches to select pod dehiscence-resistant accessions with the best haplotype and lowest genomic breeding value (GBV), respectively. While our findings could be utilized for biology, genetics, and plant breeding, selecting pod dehiscence-resistant cultivars with the optimal haplotype will need further studies to confirm additional QTLs and assess advanced GS models.